TaqMan-based real-time polymerase chain reaction assay for specific detection of bocavirus-1 in domestic cats. (October 2020) - Wang, Yong; Sun, Jianfei; Guo, Xu; Zhang, Da; Cui, Yongqiu; Li, Wei; Liu, Guangqing; Li, Yongdong; Jiang, Shudong
Abstract: Feline bocavirus-1 (FBoV-1) was first discovered in Hong Kong in 2012, and studies have indicated that the virus may cause feline hemorrhagic enteritis. Currently, there is a lack of an effective and quantitative method for FBoV-1 detection. In this study, a TaqMan-based quantitative real-time PCR (qPCR) for FBoV-1 detection was established. Primers and probes were designed to target the conserved region of the FBoV-1 NS1 gene. The sensitivity analysis indicated that the minimum detection limit was 4.57 × 10 1 copies/μL. The specificity test revealed no cross-reaction with seven other common feline viruses, including the same species—FBoV-2 and FBoV-3. The sensitivity of this method was 100 times higher than that of conventional PCR (cPCR). The established method showed good repeatability, with the intra-assay and inter-assay coefficients of variation of 0.18%–1.00% and 0.27%–0.45%, respectively. Furthermore, the analysis of feline feces revealed that the detection rate by qPCR was 7.0% (9/128), whereas that by cPCR was 4.7% (6/128). In conclusion, the established qPCR assay can quantitatively detect FBoV-1 with a high sensitivity, high specificity, and good reproducibility, making it a promising technique for the clinical detection of and basic and epidemiological research on FBoV-1. Highlights: The study establishes a TaqMan qPCR method for Feline Bocavirus-1 detection. The assay has high sensitivity, specificity and reliability. The study provides a tool that could be beneficial for clinical diagnostics of Feline Bocavirus-1 infection as well as future research on the virus.